TINDAK TUTUR DALAM EMPAT PIDATO SAMBUTAN PRESIDEN TAIWAN CAI YINGWEN - Hana Nurul Hasanah; Emilia Kurniasari (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2019)
Abstract: This research aims to identify the illocutionary acts in non-campaign speeches of the president of Taiwan, Cai Yingwen. Four speeches under the themes cross-strait and gender equality were investigated using a qualitative method. Fifty sentences were selected as data analysis, and the illocutionary acts in each sentence were identified based on Searle’s five basic categories of illocutionary act. The result shows that the opening parts of Cai speeches are moderately various contains expressive, such as thanking and congratulating, and representatives such as stating a fact, the body parts are generally dominated by representatives (stating), and the closing parts are dominated by directives such as request and order.